Modelling of multipurpose spintronic devices. (1st January 2015) - Windbacher, Thomas; Ghosh, Joydeep; Makarov, Alexander; Sverdlov, Viktor; Selberherr, Siegfried
Modelling of spin transport and spin dynamics, as a prerequisite for designing spintronic devices, is considered. Spin injection into a semiconductor under charge depletion, charge neutrality, and charge accumulation is investigated. The existence of a maximum spin current density in the bulk at a large spin current density at the interface in charge accumulation is related to the spin current at the charge neutrality condition. Then, a novel multipurpose spintronic device is proposed and its structure as well as its working principle is explained. Two important applications for this structure, a flip flop and a nano–scale oscillator, are further elucidated and the properties related to these applications are investigated.